Disseminated Mycobacterium chelonae Infection Presenting as Progressive Multifocal Osteomyelitis: Report of Two Cases and a Review of the Literature. (1994) - Oelberg, David A; Mendelson, Jack; Miller, Mark A; Dascal, Andre
Abstract : Two long term hospitalized patients developed disseminated infections caused by Mycobacterium chelonae, subspecies chelonae, over an eight-month period. In both cases, the disease was characterized by cutaneous and osseous involvement. The infections were indolent and marked by progressive bony destruction. These cases and a review of the literature are presented.